2020
DOI: 10.21577/0103-5053.20190162
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a UPLC-ESI-MS Method for Quantitation of the Anti-Alzheimer Drug Galantamine and other Amaryllidaceae Alkaloids in Plants

Abstract: Our study aimed at the development of a method based on ultra-performance liquid chromatography coupled to mass spectrometry (UPLC-ESI-MS) using selected ion monitoring for the simultaneous quantitation of the alkaloids galantamine, pseudolycorine, sanguinine and narciclasine in Amaryllidaceae species (Hippeastrum elegans, Habranthus cf. irwinianus, Hymenocallis littoralis and Griffinia nocturna). The alkaloids were extracted from dried and ground bulbs (100 mg) using liquid-liquid microextraction followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
(38 reference statements)
1
5
0
Order By: Relevance
“…de Paiva et al [28] reported the analysis of four alkaloids (galantamine, sanguinine, pseudolycorine, and narciclasine) in different Amaryllidaceae plants, and galantamine was detected in all of them [28]. Our results coincide with this observation because galantamine was detected in all of the Lycoris species.…”
Section: Discussionsupporting
confidence: 88%
“…de Paiva et al [28] reported the analysis of four alkaloids (galantamine, sanguinine, pseudolycorine, and narciclasine) in different Amaryllidaceae plants, and galantamine was detected in all of them [28]. Our results coincide with this observation because galantamine was detected in all of the Lycoris species.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, MS analysis provides more structural information on the chemical profile than the conventional chromatographic coupled to light detectors (HPLC-UV or HPLC-DAD), allowing for more confident identification. For quantitative MS analysis, the method of choice relies on tandem systems, mainly composed of triple quadrupole detectors, since higher sensitivity is achieved by monitoring specific ion transitions (the so-called multiple reaction monitoring MRM) [ 29 , 30 ]. This approach has been successfully applied in many quality control applications.…”
Section: Discussionmentioning
confidence: 99%
“…Entrance potential (EP), collision cell exit potential (CXP), and declustering potential (DP) were set at 10, 11, and 91 V, respectively. The MRM transitions monitored in the experiments is m/z 288.2 ([M + H]) for galantamine ( Suresha et al, 2014 ; de Paiva et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%